Assessment of Food Safety Regulation and Assurance System in Bangladesh’s Milk Value Chain: Addressing Discrepancies and Strategies for Improvement: Food Safety in Bangladesh’s Milk Chain: Key Challenges - Rahman, S M Rajiur; Gallo, Michele (SAARC Journal of Agriculture, 2025)
This study assesses the food safety regulation and assurance systems in Bangladesh's milk value chain, identifying discrepancies and proposing strategies for improvement. Conducted in three phases, it begins with a comprehensive review of secondary sources and consultations with experts, leading to the development and validation of checklists based on international food safety standards such as the World Organization for Animal Health (WOAH), Codex Alimentarius Commission (CAC), Hazard Analysis and Critical Control Points (HACCP), Good Animal Husbandry Practices (GAHP), Good Hygiene Practices (GHP), and the Global GAP system. These standards were harmonized with national regulations, and data were collected using actor-specific checklists via a mobile application. The final phase involved field observations, stakeholder workshops, and expert panel discussions, using triangulation and Delphi techniques to validate findings and develop improvement strategies. The study reveals distinct challenges in both the formal and informal milk marketing sectors, with the informal sector often bypassing essential safety measures. Even within the formal sector, small and medium-scale operations struggle with maintaining adequate safety protocols. Specific concerns included the lack of registration and licensing, especially for cattle and buffalo farms, and the absence of certification for milk collectors. While chilling centers and sweetmeat shops showed moderate compliance with regulatory standards, significant gaps remain in biosecurity measures, waste management, animal housing, and record-keeping. Challenges in animal health management, such as improper disposal of veterinary waste and inadequate isolation of sick animals, were prevalent. Concerns about poor hygienic practices during milking, insufficient cool chain facilities, and inconsistent use of quality control measures were also noted. Only a small proportion of chilling plants and sweetmeat shops followed proper labeling and traceability protocols, posing risks to consumer safety. To address these issues, the study recommends strengthening the regulatory framework, improving laboratory testing, and ensuring comprehensive record-keeping. A theory of change approach is proposed, focusing on capacity building, harmonizing regulations with international standards, and engaging stakeholders to improve food safety outcomes. The findings underscore the urgent need to address critical gaps in the food safety system in Bangladesh’s dairy sector to safeguard public health and promote the sustainability of the industry. SAARC J. Agric., 22(2): 257-273 (2024)